KIDNEY PHYSIOLOGY AND PATHOPHYSIOLOGY: THERAPEUTIC APPROACHES IN RENAL DISEASES (Web of Teachers: Inderscience Research, 2025)
The kidneys are vital organs responsible for filtering waste from the blood, regulating fluid and electrolyte balance, and maintaining homeostasis. Kidney diseases, including acute kidney injury (AKI), chronic kidney disease (CKD), and glomerulonephritis, can impair these functions, leading to significant morbidity and mortality. This article reviews kidney physiology and pathophysiology, focusing on the current therapeutic approaches in the management of renal diseases.